PRIMARY BUSINESS DEVELOPMENT STRATEGY OF THE INDONESIAN TEMPEH TOFU PRODUCER COOPERATIVE (PRIKOPTI) SOUTH JAKARTA - Lilis Imamah Ichdayati; Armaeni Dwi Humaerah; Beyan Mudhofar (AGRIBUSINESS JOURNAL, 2020)
This study was motivated by a decrease in the presentation of turnover with an average negative plant per of -1.4%. This negative average income growth is a problem because PRIMKOPTI's main business is the distribution of soybeans to tempeh tofu business actors. This study aims to 1) identify and analyze internal factors and external factors for PRIMKOPTI South Jakarta using the IE matrix and SWOT matrix, 2) formulate several alternatives PRIMKOPTI South Jakarta’s business development strategy uses the IE matrix and   SWOT matrix, 3) determines the most important strategy priorities in the business development of PRIMKOPTI South Jakarta using the QSP matrix. The scope of this research includes the formulation and formulation of business development strategies.The results of this study are known that there are 22 internal factors and 12 external factors of PRIMKOPTI South Jakarta that were identified.  Based on the IE Matrix, the company is in diagram I, namely the Grow or Build position. Then in Matrix SWOT, 8 strategies were obtained consisting of 2 S-O strategies, 2 W-O strategies, 2 S-T strategies, and 2 W-T strategies that can be run by the company.  Furthermore, the strategy is processed, and a strategy is obtained that the company should do by using the QSP Matrix analysis. The conclusions of this study show that PRIMKOPTI South Jakarta is in a strong internal position in sales, then the company is in a strong position / state in carrying out strategic management compete.